Is Customer Satisfaction Achieved Only with Good Hotel Facilities? A Moderated Mediation Model - Baquero, Asier (Administrative Sciences, 2023)
Modern hotel business models tend to split ownership of the property and its business operations. It can be assumed that a good-quality hotel facility per se can easily achieve high customer satisfaction. The purpose of this research was to investigate the effect of customer perception of hotel facilities on customer satisfaction by integrating the mediating effect of customer perception of the personnel and business organization and the moderating effect of the customers' family income. Three-hundred and seventy-six surveys were completed in two four-star Spanish hotels in June 2022. The PROCESS macro for SPSS was used to test the hypothesis in a moderated mediation model, using a bootstrapping method. The results showed that customer perceptions of facilities had a positive effect on their overall satisfaction, which was partially mediated by both personnel and business organization. Family income moderated the relationship between the perception of facilities and satisfaction in such a way that it was more intense in high-income customers. Medium-income customers had a more intense relationship with the perception of the personnel and business organization, together with the hotel facilities being to their satisfaction. Therefore, not only facilities, but also personnel and business organizations are important key players for achieving customer satisfaction in hotels, and family income should also be considered.
Keywords: customer satisfaction; hospitality; personnel; family income; hotel facilities; business organization; business model; globalization; consumer behavior; moderated mediation; Emerging; Scopus